Effect of daidzein and equol on DNA replication in MCF-7 cells. (15th January 2018) - Tsuji, Mako; Tanaka, Tomoki; Nagashima, Ryosuke; Sagisaka, Yuka; Tousen, Yuko; Nishide, Yoriko; Ishimi, Yoshiko; Ishimi, Yukio
Abstract: It has been reported that daidzein and equol stimulate DNA replication and proliferation of MCF-7 cells. However, their molecular mechanisms of action are still unclear. We examined the effects of daidzein and equol on DNA replication of MCF-7 cells, focusing on MCM2-7 proteins, which function as the replicative helicase. In the presence of either 1 μM of daidzein or equol, the number of cells in S-phase, which was determined by detecting bromodeoxyuridine incorporated into replicated DNA, almost doubled. The total amounts of MCM7 protein and chromatin-bound MCM7 protein increased in the presence of daidzein. The data suggest that phytoestrogens facilitate cell cycle progression in G1-phase by increasing the level of MCM proteins. In the presence of phytoestrogens, phosphorylation of Rb and levels of MCM2, 3 and 7 mRNA increased, suggesting that stimulation of MCM2-7 transcription is involved in the cell cycle progression. Under the same conditions, double-stranded DNA breakage in logarithmically growing MCF-7 cells, which was detected using anti-γ-H2AX antibodies, did not increase in the presence of equol.